Capitalization of Operating Lease Contracts in Accordance with IFRS 16 Requirements and Its Impact on the Financial Statements of Economic Entities (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to study the impact of capitalizing operating lease contracts in accordance with the requirements of IFRS 16 on the financial statements of economic entities. A sample of two industrial sector companies listed on the Iraq Stock Exchange was selected, given the importance of this sector in the Iraqi economy and its heavy reliance on operating leases to secure assets during the period from 2016 to 2023. The study included a comparison of the financial data of the sampled companies before and after the implementation of IFRS 16. Through financial data analysis, the results showed significant impacts on the balance sheet, as assets and liabilities increased due to the recognition of right-of-use assets and lease liabilities. As for the income statement, lease costs were recorded as depreciation expenses for assets and interest expenses on lease liabilities, instead of operating expenses. This resulted in changes to the final figures for profits and operating expenses, reflecting a fundamental shift in the structure of the financial statements for the two companies after applying IFRS 16. The change rate reached 23%. One of the key findings of the research is that IFRS 16 provides a comprehensive framework for capitalizing operating lease contracts and introduces substantial changes to the accounting requirements for lessees, thereby enhancing the accuracy of financial statements.